Modelos integrados de dinâmica populacional para avaliações de estoques pesqueiros de águas continentais tropicais : o caso da piraputanga do Pantanal norte. - Alves, Diego Corrêa (2012)
The mathematical and statistical advances in fitting stock assessment models enabled the emergence of the paradigm of "integrated analysis", which fits all available data to a single model of population dynamics that traditionally has total catch as the only forcing function of system. This approach, however, allowed us to include, in a flexible way, hydrology as an additional forcing function of the population dynamics of a reofilic fish in northern Pantanal. Typically hydrology is partially controlled by hydropower authorities is regulated rivers, which is the case of river Manso, upstream. Our work showed that the stock of Brycon hilarii in the northern Pantanal is not yet overfished but overfishing is occurring, and that both the recruitment and the spawning biomass also be dependent upon the hydrology. The use of integrated models contributed to the advancement of knowledge of population ecology of migratory fish. It is recommended that the stocks of the northern Pantanal be systematically monitored in order to allow for periodic assessments of the stock status for the main fished species and that inland fisheries management be integrated into the hydrology management.